An investigation on corrosion of piping material for apartment / Aimi Hazirah Ab Rahim - Ab Rahim, Aimi Hazirah (2012)
Corrosion is a natural process and cannot be prevented in plumbing system. The natural environments with the presence of water and oxygen combined with the steel will formed the corrosion exist and this situation will give effects towards the users. In my research, I try to find out the types of material and the problems happened in plumbing system affected by the corrosion towards the building and users that have been researched. The information was done by an interviews and observation to the maintenance office of the building. For the conclusion and recommendation, I give my opinion based on the research and information that I get to ensure and avoid the corrosion problems can be reduce in the building for the future performance of the building.